2020
DOI: 10.1115/1.4048817
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Stage Design Framework for Two-Dimensional Spatial Packing of Interconnected Components

Abstract: Packing and routing separately are each challenging NP-hard problems. Therefore, solving the coupled packing and routing problem simultaneously will require disruptive methods to better address pressing related challenges, such as system volume reduction, interconnect length reduction, ensuring non-intersection, and physics (thermal, hydraulic, or electromagnetic) considerations. Here we present a novel two-stage sequential design framework to perform simultaneous physics-based packing and routing optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Of course, the reliable operation of all electrical components must be ensured, which primarily includes sufficient cooling of the power semiconductors. Prior research has demonstrated new concepts for optimizing component placement to reduce electrical pathways and device temperatures [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the reliable operation of all electrical components must be ensured, which primarily includes sufficient cooling of the power semiconductors. Prior research has demonstrated new concepts for optimizing component placement to reduce electrical pathways and device temperatures [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo simulations are used to optimize component positions and metal heat spreader dimensions for a high-density design. Compared to optimization approaches of prior research [9]- [11], the temperature of the housing is identified as the limiting factor.…”
Section: Introductionmentioning
confidence: 99%